(untitled) (Singaporean Journal of Business Economics and Management, 2015)
The Namibian government, in particular its health sector continues to face serious challenges in delivery equitable services, despite the government (GRN) investing many resources in its health sector since independence with the aim to revamp its fragmented health care and social welfare system inherited at independence. It is not always feasible for single organisations to produce all the inputs it requires on its own, therefore, the trend is to consider outsourcing, partnership, or strategic alliances with others in rolling out programmes. The trend for most governments is to consider PPPs in order to complement scarce resources, such as skills, finances and to get new innovations from private companies. MoHSS has been considering implementing PPP to benefit from the aforementioned gains. Attitudes and perceptions can have an influence on how PPP is seen and these can in turn impact on the success or failure of this programme and this study assessed the attitudes and perceptions of the private sector towards PPP of the Namibian health sector.